A combination of metformin and insulin improve cardiovascular and cerebrovascular risk factors in individuals with type 1 diabetes mellitus. (September 2022) - Xu, Linlin; Wang, Wei; Song, Wei
Abstract: Background: This study aims to further clarify whether the addition of metformin to insulin treatment improve cardiovascular and cerebrovascular risk factors in individuals with T1DM. Methods: Electronic databases were searched for randomized controlled trials in which the efficacy and safety of metformin were compared with those of a placebo for risk factors of cardiovascular and cerebrovascular disease among individuals with T1DM, and a meta-analysis was conducted. Results: Thirteen cardiovascular studies were identified. In the metformin group, mean carotid intimal media thickness was significantly reduced by 0.03 mm, ascending aortic pulse wave velocity by 6.3 m/s, descending aortic wall shear stress by 1.77 dyn/cm 2 (P = 0.02), insulin daily dose by 0.05 U/kg/d, body weight by 2.27 kg, fat-free mass by 1.32 kg, body mass index by 0.58 kg/m 2, hip circumference by 0.29 m, and low-density lipoprotein by 0.16 mmol/L, all above are P < 0.05. In the metformin group, flow-mediated dilation was increased by 1.29 %, glucose infusion rate/insulin by 18.22 mg/(kg⋅min)/μIU/μL, and waist-to-hip ratio by 0.02, all above are P < 0.00001. The metformin group showed no differences in blood pressure, reactive hyperemia index, waist circumference, triglyceride, total cholesterol, high-density lipoprotein cholesterol, or body mass index Z score. For cerebrovascular studies were identified. But none of them had a risk factor assessment. Conclusions: Metformin can ameliorate cardiovascular and cerebrovascular risk factors through non-hypoglycemic multiple pathways in individuals with T1DM.